PENGARUH MOTIVASI INTRINSIK, MOTIVASI EKSTRINSIK, LINGKUNGAN KERJA DAN BUDAYA ORGANISASI TERHADAP KINERJA KARYAWAN RUMAH SAKIT ISLAM BANJARNEGARA - Nur Wakhidah Lulu’ul Jannah; Hermin Endratno (Lembaga Publikasi Ilmiah dan Penerbitan (LPIP), 2017)
This research aimed to partially and simultaneously analyze: 1) intrinsic motivation towards the employees’ performance, 2) extrinsic motivation towards the employees’ performance, 3) working environment towards the employees’ performance, 4) organization culture towards then employees’ performance, 5) intrinsic motivation, extrinsic motivation, working environment and organization culture toward the employees’ performance. It was a survey research. This research was conducted in Rumah Sakit Islam Banjarnegara with 100 employees as the respondents of the research are: 1) intrinsic motivation has no significant effect towards the employees’ performance, 2) extrinsic motivation has no significant effect towards the employees’ performance, 3) working environment has significant effect towards the employees’ performance, 4) culture has significant effect towards the employees’ performance, 5) intrinsic motivation, extrinsic motivation, working environment and organization culture has significabt effect toward the employees’ performance. Keywords: Intrinsic Motivation, Extrinsic Motivation, Working Environment, Organization Culture, Employees’ Performance